A Comparison of Routing Protocol for WSNs: Redundancy Based Approach A Comparison of Routing Protocol for WSNs: Redundancy Based Approach - Anand Prakash (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2014)
Wireless Sensor Networks (WSNs) with their dynamic applications gained a tremendous attention of researchers. Constant monitoring of critical situations attracted researchers to utilize WSNs at vast platforms. The main focus in WSNs is to enhance network localization as much as one could, for efficient and optimal utilization of resources. Different approaches based upon redundancy are proposed for optimum functionality. Localization is always related with redundancy of sensor nodes deployed at remote areas for constant and fault tolerant monitoring. In this work, we propose a comparison of classic flooding and the gossip protocol for homogenous networks which enhances stability and throughput quiet significantly.